2016
DOI: 10.1007/s40003-016-0225-7
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Round Fruited Brinjal for Export from Eastern India

Abstract: Brinjal has immense potential for the development of desirable recombinants for export trade through heterosis breeding. Therefore, half-diallel mating design involving six optimally diverse parents was used to determine heterosis, dominance reaction, combining ability, and gene action for eleven quantitative traits in brinjal. The predictability ratio revealed overwhelming response of non-additive gene action for conditioning of all the studied traits, suggesting that heterosis breeding could be used for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The maximum number of fruit per plant was produced by 13/BRBW/RES-3 (21.11) and the minimum was recorded in 2012/BRBW . Wide variations in quantitative characters of brinjal genotypes tested previously in the Gangetic plains of West Bengal were also recorded by Das et al, (2010), Chattopadhyay et al, (2011), Shende et al, (2016 and Dutta et al, (2018). It was found that bacterial wilt resistance in brinjal is tightly linked with small fruit size.…”
Section: Reaction Of Genotypes Against Bacterial Wilt Diseasesupporting
confidence: 59%
“…The maximum number of fruit per plant was produced by 13/BRBW/RES-3 (21.11) and the minimum was recorded in 2012/BRBW . Wide variations in quantitative characters of brinjal genotypes tested previously in the Gangetic plains of West Bengal were also recorded by Das et al, (2010), Chattopadhyay et al, (2011), Shende et al, (2016 and Dutta et al, (2018). It was found that bacterial wilt resistance in brinjal is tightly linked with small fruit size.…”
Section: Reaction Of Genotypes Against Bacterial Wilt Diseasesupporting
confidence: 59%
“…An important limiting factor in establishing a founder population is the likelihood of a male and a female emerging in temporal and spatial proximity to locate each other and mate. Recall that border interceptions of insects are a poor predictor of successful establishment (Kenis et al., 2007 ; Caley et al., 2015 ).…”
Section: Figure A1mentioning
confidence: 99%
“…Brinjal is referred as the king of vegetables due to its wide utility in various dishes (Kumar et al, 2020) and as eggplant. It is one of the main sources of reliable revenue for small farmers (Shende et al, 2016).…”
Section: Introductionmentioning
confidence: 99%